The Synthesis of New Neutron-Rich Heavy Nuclei - Loveland, Walter David (Frontiers in Physics, 2019)
All the known isotopes of the elements Fm through Og are neutron-deficient relative to β-stability. In this contribution, I discuss two methods of producing more n-rich heavy nuclei, i.e., the use of radioactive nuclear beams (RNBs) and the use of multi-nucleon transfer (MNT) reactions. In the former case, I discuss recent studies of the interaction of 39,46K with 181Ta and their implications for the synthesis of more n-rich isotopes of Bh and Hs. In the case of MNT reactions, I discuss recent results for the reaction of 136Xe with 208Pb, 204Hg + 198Pt, and 136Xe + 198Pt. I compare measured distributions of the target-like fragments (TLFs) and projectile-like fragments (PLFs) with current models of MNT reactions.